Stages of Prosecution of Crimes with Aggravation Analysis of Religious Court Decisions - Aldi, Muhammad; Hakim, Abdul; Jannah, Maya (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
The state guarantees the lives of its citizens in accordance with Article 28A of the 1945 Constitution. The Criminal Code covers specific crimes including crimes against property in Book Two Chapter XXII, namely Theft. The purpose of this study is to analyse the prosecutor's charges in a case of aggravated theft. The method used in this research is normative research. This type of research uses descriptive qualitative type. The data sources used are two types of primary data sources in the form of case file Number: 814/pid.B/2023/PN.Rap and criminal law books and secondary data sources in the form of books and articles related to this research. The results of this study are the unbalanced prosecutor's charges between the two perpetrators of theft with aggravation. This research concludes that the legal considerations in the judge's decision which sentenced each of the two defendants to 1 year (defendant 1) and 9 months (second defendant). This research is strengthened by the existence of case files located at the Labuhanbatu police station, so that it can be properly analysed.